Engaging the African American Church to Improve Communication About Palliative Care and Hospice: Lessons From a Multilevel Approach. Issue 3 (July 2019) - Johnson, Jerry; Hayden, Tara; Taylor, Lynne Allen; Gilbert, Arthur; Jones, Cedric Hughes; Mitchell, Marshall Paul Hughes; Curtis, Brenda
Background: As the spiritual family for many African Americans, the church presents an opportunity to improve communication about palliative care and hospice (PCH). However, sustainable change in church-based, practices related to PCH requires a compreshensive, multilevel approach. Objectives: Our primary goal was to encourage churches to embrace palliative care and hospice as acceptable alternatives for end-of-life care by creating venues to improve communications about PCH. This paper compares our experience in 5 churches, revealing lessons learned and the challenges of engaging, implementing, and maintaining a multilevel approach in the churches, and our strategies in response to those challenges. Design: Descriptive study Settings/Subjects: We partnered with 5 African American Churches in the Philadelphia Region. We targeted pastors, other church leaders, and congregants. Methods: We created 1) a leadership-education program, 2) an intensive training program for church-based lay companions (health visitors), and 3) messages and materials to increase knowledge and influence attitudes about PCH. Results: We impacted church structures and policies as shown by: integration of the project activities into existing church structures, new church-based programs dedicated to training lay companions and church leaders, new roles for church members (church liaisons) dedicated to this project, and new materials and messages focusing on PCH for the general congregation. Conclusions: We demonstrated the feasibility of engaging the African American church in a comprehensive, multilevel process designed to improve communication about palliative care and hospice (PCH). Our success demonstrates the potential of the African American church as a community resource for lay education about PCH.